Nursery stock and its effect upon orchards - Cunningham, Jules Cool (My University, 1905)
Introduction: The United States is becoming the greatest fruit consuming nation in the world. The interest in the work of planting parks and lawns as well as landscape gardening is increasing year by year and we hope Professor John Craig of Cornell University is right when he says "Beautiful America is coming." In traveling through the eastern portion of the United States one especially notices the lack of young orchards and that the old orchards that have yield such large return must soon be replaced. Throughout the irrigation districts, as well as in the Southern Central states, large commercial orchards are being planted every year. One of the most important features of orchard work is the increasing number of "Small Family" orchards. More and more do our people realize the pleasure and profit of having fresh, home grown fruit for family table use. To furnish well-formed trees, free from disease or injury and true to label is the mission of the nurseryman. In considering the effect of nursery stock upon the subsequent trees and shrubs only a few of the most prominent features will be discussed. Tree Breeding. We might properly speak of this as the "Thoroughbred Age" Animals, grain and even trees must have "pride of ancestry" before they meet with the approval of the progressive American. No doubt the term "pedigreed trees" has been used to increase business yet every honest nurseryman will exercise the greatest care in the selection of scions, buds, cuttings and seeds to be used in propagation. In fruit plantations it, is a well-known fact that some trees will produce superior fruit in size, flavor or color to others of the same variety. Just how far this characteristic will be transmitted by buds or scions is not definitely known. It seems reasonable to assume however that better results will be obtained if the nurseryman propagates from the tree yielding the best fruit.
Citation: Cunningham, Jules Cool. Nursery stock and its effect upon orchards. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Tree Breeding; Winter Injury; Clytocybe Parasitica; Theses